Atmospheric curing of zinc sulfide concentrate by sulfuric acid below 300℃ - Ma, ruixin; Deng, fanlei; Xu, guixiao; Fan , wenwen; Li, shina (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
In an open-air condition, zinc sulfide concentrate from Yunnan province, P R China, was cured with sulfuric acid at different acid-to-ore ratio and heated to 220℃~260℃ for different time, then leaching the cured product. The effects of temperature, curing time, acid-to-ore ratio, sulfuric acid concentration on the leaching ratio of zinc (hZn) were studied. The results showed that hZn could reach as high as 98.23% under the optimized conditions of temperature 240℃, curing time 2.5 hours, acid-to-ore ratio 1.4:1 and sulfuric acid concentration 60wt%. The leaching residue ratio is 6% composed mainly of silicate. The kinetic results confirm the zinc concentrate accord with shrinking core model controlled by the interface chemical reaction with an apparent activation energy of 43.158 kJ/mol.